Uji Daya Hambat Ekstrak Etanol Daun Jerangau Hijau terhadap Staphylococcus aureus: The Inhibitory Test of Ethanolic Extract of Jerangau Hijau Leaves against Staphylococcus aureus - Susi Novaryatiin; Guntur Satrio Pratomo; Cindia Yunari (Borneo Journal of Pharmacy, 2018)
Jerangau Hijau is a medicinal plant believed by the people of Central Kalimantan to have an efficacy of treating fever, postpartum injuries, and anti-inflammatory. Based on previous research, Jerangau Hijau is known to contain chemical compounds namely flavonoids and saponins that have activity as an antibacterial. The purpose of this study was to find out whether the ethanolic extract of Jerangau Hijau leaves able to inhibit the growth of Staphylococcus aureus bacteria and to know the concentration of ethanolic extract of Jerangau Hijau leaves that able to inhibit the growth of Staphylococcus aureus bacteria. This research was conducted using the Kirby-Bauer method with disc paper. The extraction process was carried out by percolation method using 96% ethanol solvent. The results showed that the ethanolic extract of Jerangau Hijau leaves was able to inhibit the growth of Staphylococcus aureus bacteria, at concentrations of 1%, 5%, 10%, and 15% with mean inhibitory zones respectively 22±0.2 mm; 32.3±1.4 mm; 26.5±3.8 mm; and 13.1±3 mm.